Outcome of Transforaminal Epidural Injections in Patients with Lumbar Radicular Pain - Arshan Munir, Inam Ur Rahim, Arzoo Rahim, Mohammad Farooq, Haris Azeem Khan, Waleed Ali, Mamoon Sattar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Backache is quite a common problem in adults.one of the common reasons for this is compression on nerve roots due to disc bulge. The pain may start from back and radiate to legs. Objective: The study aimed to evaluate the efficacy of corticosteroids when injected by transforaminal route. Study design: This descriptive study was conducted at Orthopedic Unit 2 Mayo Hospital Lahore. The duration of the study was six months from January 2018 to June 2018. Material and Methods: The study was conducted on the 127 patients attended the orthopedic department of our institute hospital. The ethical and review board committee of the hospital approved the study. Every participant was informed about the study and they willingly signed the written consent. According to the inclusion criteria the patients of age above than 18 diagnosed with the lumber pain. The 127 patients of both genders that were included in the study were given transforaminal epidural injections (TEI). The results were studied after 4 weeks. The pain reduction was scored using Oswesrty Disability Index (ODI). The age range of the patients included in the study was from 20 to 80 years. SPSS 5 was used for statistics analysis of the data collected. Results: The calculated mean ODI of patients at the start was 73.90+ and after four weeks it was reduced to 27.62-+8.66. The mean ODI score at baseline of the patients was 73.90±7.64 with lowest and highest value of 46 & 94 respectively. The average ODI score at 4th week of the patients was 27.62±8.66 with lowest and highest values of 10 & 60. The study results showed that the average reduction of ODI from baseline to 4th week of the patients was 46.29± 10.98 with lowest and highest reduction of 20 & 68. Conclusion: This study concluded that a significant reduction in mean pain score was noted with transforaminal Injections in patients with lumbar radical pain. It can be recommended to be used in patients with lumbar radical pain. The pain reduction was statistical significant after TEI. Keywords: Transforaminal epidural injection, Oswesrty score, lumbar radicular pain.